"Efeitos anti-inflamatório e antirreabsortivo ósseo da Punica granatum l. combinada ou não com laser de baixa intensidade na perda óssea induzida por ligadura em ratos” - Monteiro, Larice Kércia Braz (2013)
Periodontitis is a chronic infectious inflammatory disease. P. granatum (PNG) and low level laser irradiation (LLLI) have demonstrated anti-inflammatory properties and antioxidants. The aim of this study was to evaluate the anti-inflammatory and bone antiresorptive activities of PNG combined or not with LLLI in ligature-induced periodontitis in rats. Periodontitis was induced in 72 rats by inserting a nylon-3.0 around the left upper second molar. The contralateral hemimaxila was used as control. Groups of 6 animals received saline 0.9% (SAL), SAL+LLLI 4 J/cm2, PNG [60, 180, 540 (mg/kg)] or PNG 540 mg/kg+LLLI 4 J/cm2. The low intensity laser GaAlAs was applied immediately after surgery, while PNG was administered by gavage daily until day 11, when the animals were killed. The jaws were removed and processed for macroscopic, histometric, histological and immunohistochemical staining for TRAP. Gingival tissue samples were obtained to evaluate the activity of myeloperoxidase (MPO). Blood samples were collected for measurement of serum bone alkaline phosphatase (BALP), leukograms and analysis of liver and kidney function. Additionally, indexes of liver and kidney were performed. Rats were weighted daily. Periodontitis induction caused intense alveolar bone loss (ABL), reduction of BALP, cementum and periodontal ligament destructions, and intense leukocyte infiltration. Systemically, periodontitis induced leukocytosis and and did not alter hepatic transaminases, urea or creatinine serum levels, or liver and kidney indexes. The ABL was prevented by PNG (60= 34%, 180= 34%, 540= 42%), SAL+LLLI= 31% e PNG 540+LLLI= 48% (p<0.05). PNG 540 combined or not with LLLI decreased the alveolar bone resorption, the leukocyte infiltration and preserved the periodontium in the jaws in which the periodontitis was induced. Animals treated with PNG 540+LLLI showed an important decreasing of TRAP positive immunostaining (Periodontium Unchallenged = 0.0 ± 0.0, SAL= 0.016 ± 0.004; SAL+LLLI= 0.01 ± 0.003; PNG 540= 0.011 ± 0.003; PNG 540+LLLI = 0.002 ± 0.0003). The raise of MPO activity was prevented by PNG (60= 46%, 180= 49%, 540= 76%), SAL+LLLI= 54% e PNG 540+LLLI= 80% (p<0.05). In spite the reduction of BALP, seen in SAL group was not prevented by SAL+LLLI or PNG (p>0.05), the combined treatment with PNG 540+LLLI caused an increase on BALP serum levels (74.2 ± 5.4 U/l), when compared to SAL (44.9 ± 3.0 U/l) (p<0.05). No change was seen for hepatic transaminases, urea or creatinine serum levels, or in liver and kidney indexes, in all groups (p>0.05) and all groups prevented (p<0.05) the leukocytosis observed in SAL group. In short, PNG combined or not with LLLI reduced leukocyte infiltration and the number of neutrophils and reduced alveolar bone loss, at the expense of inhibiting osteoclast activation, without causing systemic changes